The Difference in the Effects of Dry Needling (DN) and Low Level Laser Therapy (LLLT) on Pain Reduction in Upper Trapezius Spasms - Anggit Laksita Dewi; Saifudin Zuhri; Aditya Johan R (Jurnal Keterapian Fisik, 2023)
Background: Upper trapezius muscle spasm pain often occurs due to excessive forward head posture and persistent muscle tension, thereby hindering functional activities. Various physiotherapy modalities are used to reduce pain, including Dry Needling (DN) and Low Level Laser Therapy (LLLT). The purpose of this study was to compare the effectiveness of DN and LLLT in reducing upper trapezius muscle spasm pain. Methods: This study was an experiment with a two-group pre- and post-test design. A sample of 30 patients from the Physiotherapy Clinic at Dr. Ramelan Hospital in Surabaya was selected using simple random sampling and divided into two groups of 15 people each. Group I received DN intervention, while group II received LLLT for four weeks at a frequency of three times per week. The research instrument used the Visual Analog Scale (VAS), which has a reliability of 0.97 and validity of 0.925. Data analysis was performed using the paired sample t-test and independent sample t-test. Results: There was a significant difference between the VAS scores before and after treatment in both groups (p=<0.001). The pain reduction score was higher in the DN group (Δ=3.5) than in the LLLT group (Δ=1.75), proving that DN is more effective in reducing upper trapezius muscle spasm pain. Conclusion: DN is more effective than LLLT in reducing upper trapezius muscle spasm pain. DN intervention can be used as the primary choice in the management of neck muscle spasm and combined with therapeutic exercises for optimal results.